India's education policy: From national to commercial - Panikkar, K.N. (2011)
Post independence, India's leaders, particularly Abul Kalam Azad, advocated an education policy that would be liberal and humanitarian, and set the nation on the path of progress and prosperity. This path was neither a full continuation of the colonial modern nor a restoration of the feudal-traditional. Drawing on progressive ideas from India's "renaissance" and freedom struggle within the Indian "renaissance" and nationalism, this education policy was meant to unleash the potential of India's civilisation by a process of intellectual decolonisation. Unfortunately, in the past few decades, this unfinished agenda has been dumped by successive governments. It has been replaced by an educational policy which priorities private profit over public good and will encourage cultural and intellectual imperialism. - Reproduced.
Keywords: India - Educational policy; Educational policy